2022
DOI: 10.1021/acs.accounts.2c00346
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Contrast Agents for Magnetic Resonance Molecular Imaging of Cancer

Abstract: Conspectus Magnetic resonance imaging (MRI) is a clinical imaging modality that provides high-resolution images of soft tissues, including cancerous lesions. Stable gadolinium­(III) chelates have been used as contrast agents (CA) in MRI to enhance the contrast between the tissues of interest and surrounding tissues for accurate diagnostic imaging. Magnetic resonance molecular imaging (MRMI) of cancer requires targeted CA to specifically elucidate cancer-associated molecular processes and can provide high-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 73 publications
0
30
0
Order By: Relevance
“…ZD2 specificity for EDB-FN has been validated and used in the development of a targeted gadolinium-based contrast agent ZD2-N3-Gd­(HP-DO3A), MT218, for magnetic resonance molecular imaging (MRMI) of cancer . MRMI with MT218 can distinguish between aggressive and nonaggressive cancers based on EDB-FN expression. , The ZD2 peptide has shown high specificity to bind to abundant EDB-FN in the tumor ECM for cancer molecular imaging in multiple cancer models. It is also a promising candidate for functionalizing nanoparticles for enhanced delivery of siRNA to regulate lncRNA DANCR in TNBC …”
Section: Introductionmentioning
confidence: 99%
“…ZD2 specificity for EDB-FN has been validated and used in the development of a targeted gadolinium-based contrast agent ZD2-N3-Gd­(HP-DO3A), MT218, for magnetic resonance molecular imaging (MRMI) of cancer . MRMI with MT218 can distinguish between aggressive and nonaggressive cancers based on EDB-FN expression. , The ZD2 peptide has shown high specificity to bind to abundant EDB-FN in the tumor ECM for cancer molecular imaging in multiple cancer models. It is also a promising candidate for functionalizing nanoparticles for enhanced delivery of siRNA to regulate lncRNA DANCR in TNBC …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that compared with passive target delivery, decoration with active targeting ligands (including cRGD, RGD, or RGD2), which can actively identify specific receptors on the target cell, is efficient. [17] Wang et al [18] constructed a chain-like nanoprobe (APP-Ag2S-RGD) that can be used to identify tumor margins for precise tumor resection of PM. However, the efficiency of this targeted delivery is easily diminished, which is attributed to the non-specific uptake of nanoparticles by non-cancerous cells.…”
Section: Targeted Magnetic Resonance Imaging/near-infrared Dual-modal...mentioning
confidence: 99%
“…Studies have shown that MONs can mimic the characteristics of POD, CAT, and SOD. Among various MONs, MnO 2 nanostructures have attracted considerable attention as stimuli-responsive and biodegradable materials [ 150 , 151 ]. In the TME, MnO 2 can react with GSH, H + ions, and H 2 O 2 to generate Mn 2+ ions, playing multiple roles in tumor diagnosis and treatment.…”
Section: Nanozymes For Molecular Imagingmentioning
confidence: 99%